2021
DOI: 10.1186/s13045-021-01091-5
|View full text |Cite
|
Sign up to set email alerts
|

TET2 and DNMT3A mutations and exceptional response to 4′-thio-2′-deoxycytidine in human solid tumor models

Abstract: Background Challenges remain on the selection of patients who potentially respond to a class of drugs that target epigenetics for cancer treatment. This study aims to investigate TET2/DNMT3A mutations and antitumor activity of a novel epigenetic agent in multiple human cancer cell lines and animal models. Methods Seventeen cancer cell lines and multiple xenograft models bearing representative human solid tumors were subjected to 4′-thio-2′-deoxycyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Clonogenic cell survival assay. The test has been described in detail previously 41 . Briefly, 150,000 cells were treated with increasing concentrations of DNMTi for 48 h. After washing, 2,000 cells/well in triplicates were plated in 6 wells plates for 8-14 days.…”
Section: Dnmt1 Gene Disruption In Mcf7 Cells By Crispr Methodmentioning
confidence: 99%
See 1 more Smart Citation
“…Clonogenic cell survival assay. The test has been described in detail previously 41 . Briefly, 150,000 cells were treated with increasing concentrations of DNMTi for 48 h. After washing, 2,000 cells/well in triplicates were plated in 6 wells plates for 8-14 days.…”
Section: Dnmt1 Gene Disruption In Mcf7 Cells By Crispr Methodmentioning
confidence: 99%
“…Western blotting. Western blotting method has been described previously 41 . Briefly, 50 µM of protein were electrophoresed on 7.5% or 4-20% SDS-polyacrylamide gels (Bio-Rad, Hercules, CA, USA).…”
Section: Cell Cycle Analysismentioning
confidence: 99%
“…Besides, Yang demonstrated that concurrent mutations in TET2 and DNMT3A were sensitive to T-dCyd treatment in vitro and in vivo. 39 For copy number variations, the RMCS2 contained higher CNV amplification and deletion frequencies than the RMCS1. Some RNA modification-related genes were contained in these mutated regions, such as HNRNPAB, CDKN2B, and FGFR4.…”
Section: Discussionmentioning
confidence: 95%
“…TET2 could suppress VHL deficiency‐driven clear cell RCC by inhibiting HIF signaling. Besides, Yang demonstrated that concurrent mutations in TET2 and DNMT3A were sensitive to T‐dCyd treatment in vitro and in vivo 39 . For copy number variations, the RMCS2 contained higher CNV amplification and deletion frequencies than the RMCS1.…”
Section: Discussionmentioning
confidence: 98%
“…Second, the variations in other associated genes might effected the phenotypes of DNMT3A. It is evident that there are some genes frequently co-occurrence with DNMT3A variants in haematopoietic malignancy including FLT3, TET2, NPM1, IDH1, IDH2, JAK2 and CEBPA [4,[12][13][14][15][16], while in neurodevelopmental disorders including MeCP2, NSD1 [17][18][19]. Polonis [20] describe a 5-year-old female with a paternally inherited pathogenic variation in EZH2 (c.2050C > T, p.Arg684Cys) and a maternally inherited 505-kb duplication of uncertain signi cance at 2p23.3 (encompassing ve genes, including DNMT3A) who presented with intrauterine growth restriction, slow postnatal growth, short stature, hypotonia, developmental delay, and neuroblastoma diagnosed at the age of 8 months.…”
Section: Discussionmentioning
confidence: 99%